[OP.3D.04] ACTIVATED CD4+ AND CD8+ T-CELL SUBPOPULATIONS IN PATIENTS WITH PRIMARY HYPERALDOSTERONISM AND TRUE RESISTANT HYPERTENSION. (September 2016) - Kaszuba, A.; Konior, A.; Mikolajczyk, T.; Prejbisz, A.; Kabat, M.; Cendrowska-Demkow, I.; Dobrowolski, P.; Pregowska-Chwala, B.; Michel-Rowicka, K.; Klisiewicz, A.; Michalek, P.; Toutounchi, S.; et al.
Abstract : Objective: Role of the T cells in pathogenesis of hypertension has been demonstrated in numerous mouse models, limited data is available in human hypertension. Therefore the aim of our study was to quantify blood T lymphocyte subsets, characterized by expression of CD25 markers (CD3 + , CD8 + and CD3 + CD4-CD8- cells) and expression of perforin and granzyme (in CD8 + cells) in subjects with primary hyperaldosteronism (PA), resistant hypertension (RHT) characterized by increased cardiovascular risk and excessive amounts of circulating aldosterone in comparison to controls matched for age, sex and BMI(control group, CG). Design and method: In an ongoing study we included so far 18 patients (10 M, 8F, mean age 54.7 ± 12.7) with PA and 20 patients (11 M, 9F mean age 53.6 ± 15.9) with RHT and 13 (11 M, 2F, mean age 51.9 ± 8) control subjects (CG). T cell characteristics from peripheral blood samples was studied by multicolour flow cytometry with intracellular staining for perforin and granzyme. Results: In comparison to CG, both patients with PA and RHT had significantly higher percentage of CD25 + subsets in: total CD3 + T-cell population (31.1 ± 6, 2% and 32.2 ± 9.0% vs CG 20.2 ± 7, 0%, p < 0.001 and p < 0.001), CD4 + T cell subpopulation and were almost doubled within the CD8 + T cell subpopulation (8.0 ± 3.3% and 7.0 ± 5.7% vs CG 4.1 ± 3.6%, p = 0.01 and p = 0.03); Simularly CD25 + expression was increased in double negative T cell subpopulation (5.1 ± 2.5% and 4.1 ± 2.9% vs CG 2.4 ± 1.7%, p = 0.01 and p = 0.022). To further investigate activation status within the CD8 + cells we observed very significantly increased CD8 + Perforin + T cells (5.6 ± 8.3% and 6.8 ± 8.0% vs CG 0.9 ± 0.7%, p = 0.034 and p = 0.004) and granzyme + cells. Conclusions: This is the first report of increased content of CD25 + T cell subsets (CD4 + ; CD8 + and CD4-CD8-) in PH and RHT. Our results for the first time indicate, that T cell activation is dysregulated with very significant increase of cytotoxic CD8 + T cells expressing granzyme and perforin. Further studies are needed to establish whether these cells are involved in the pathogenesis of PA and true RHT.